Nanoporous Cathode Material for High-Energy-Density Sodium-Ion Batteries - Ding, Haiyang; Li, Hao; Tao, Qingdong; Ren, Jianhui; He, Jiafeng (ACS applied nano materials, 2024)
A promising cathode material has been developed for sodium-ion batteries (SIBs): NASICON-type Na3V2(PO4)3 (NVP). However, replacing V with a low-cost, environmentally friendly metal ion is an immediate priority for Na3V2(PO4)3 (NVP) industrialization. In this paper, we synthesize a nanoporous vanadium-based polyanion cathode material by a mechanochemical method. Na3.5V1.5Mn0.5(PO4)3/C (NVMP/C-0.5) shows excellent electrochemical performance and has almost no Jahn–Teller effect. NVMP/C-0.5 has an initial discharge capacity of 136.2 mAh g–1 at 0.1C, and a plateau voltage of 3.5 V. In addition to exhibiting excellent rate performance (96.4 mAh g–1 at 20C), the NVMP/C-0.5 exhibits long cycle capability (64.7% of the capacity is retained after 8000 cycles at 20C). Ex situ X-ray photoelectron spectroscopy (XPS) tests demonstrate that V3+/V4+, V4+/V5+, and Mn2+/Mn3+ redox pairs are all involved in redox reactions. Ex situ X-ray diffraction (XRD) tests reveal that NVMP/C-0.5 has high structural reversibility and a small volume change in the charge–discharge reaction. With its high energy density, NVMP/C-0.5/hard carbon full cells have the potential for use in sodium-ion batteries.